2011
DOI: 10.4236/ijcm.2011.22030
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Muscle Function Does Not Predict Mitral Regurgitation in Patients with Normal Left Ventricular Systolic Function: A Transesophageal Echocardiographic Study

Abstract: Objective: To evaluate LV papillary muscles (PM) function using transesophageal echocardiography (TEE), and to determine the relationship between PM function and mitral regurgitation in patients with normal left ventricular sys-tolic function. Design: TEE examinations were prospectively performed. End diastolic and end systolic PM lengths were obtained from the transgastric long axis views and fractional systolic shortening (FS) was calculated. LV ejection fraction was determined using modified Simpson rule an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In line with previous studies, PapMI was a nonsignificant predictor of the presence and severity of MR. 4 There is strong experimental evidence that isolated papillary muscle dysfunction in an adequately contractile ventricle is not associated with significant MR. 10 Furthermore, several human studies using echocardiography found no correlation between mild MR and papillary muscle dysfunction. 11,12 Consequently, echocardiography and CMR studies, including our study, have unequivocally demonstrated that PapMI is not obligatorily associated with ischemic MR.…”
Section: Prognostic Significance Of Papmimentioning
confidence: 99%
“…In line with previous studies, PapMI was a nonsignificant predictor of the presence and severity of MR. 4 There is strong experimental evidence that isolated papillary muscle dysfunction in an adequately contractile ventricle is not associated with significant MR. 10 Furthermore, several human studies using echocardiography found no correlation between mild MR and papillary muscle dysfunction. 11,12 Consequently, echocardiography and CMR studies, including our study, have unequivocally demonstrated that PapMI is not obligatorily associated with ischemic MR.…”
Section: Prognostic Significance Of Papmimentioning
confidence: 99%
“…Loss of this contractile action results from myocardial infarction with subsequence papillary muscle fibrosis or ischemia 4 . But previous studies5, 6 delineated that there is minimal or no correlation between papillary muscle dysfunction and mitral regurgitation, especially in those patients where left ventricular chamber size and function is normal.…”
Section: Introductionmentioning
confidence: 99%
“…The impairment of the subvalvular apparatus is detrimental to the left ventricular systolic function and mitral regurgitation. 3 , 4 Papillary muscle dysfunction has previously been shown as a mechanical cause of mitral regurgitation in patients with functional mitral regurgitation (FMR) in some studies, but, in some others, no correlation was found between mitral regurgitation and papillary muscle dysfunction and even an attenuating effect of papillary muscle dysfunction was reported in most studies. 2 , 3 , 5 - 8 In experimental studies, under the range of normal loading and inotropic conditions, papillary muscle contraction normally follows the general characteristics of left ventricular contraction, 4 but ischemia or stunning may disrupt this course.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Papillary muscle dysfunction has previously been shown as a mechanical cause of mitral regurgitation in patients with functional mitral regurgitation (FMR) in some studies, but, in some others, no correlation was found between mitral regurgitation and papillary muscle dysfunction and even an attenuating effect of papillary muscle dysfunction was reported in most studies. 2 , 3 , 5 - 8 In experimental studies, under the range of normal loading and inotropic conditions, papillary muscle contraction normally follows the general characteristics of left ventricular contraction, 4 but ischemia or stunning may disrupt this course. It is reported that in ischemic mitral regurgitation, diminished papillary muscle shortening, which is termed as papillary muscle dysfunction, paradoxically decreases the degree of MR. 5 , 7 In patients with normal LV function and MR, fractional shortening has been shown to be normal, similarly to patients with mild or more severe MR. 3 In patients with degenerative mitral regurgitation (DMR), there is no sufficient knowledge about the role of papillary muscle (PM) dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation